Drug use and childhood-, military- and post-military trauma exposure among women and men veterans. (1st July 2015) - Kelley, Michelle L.; Brancu, Mira; Robbins, Allison T.; D'Lima, Gabrielle M.; Strauss, Jennifer L.; Curry, John F.; Fairbank, John A.; Runnals, Jennifer; ,
Highlights: Non-combat and combat trauma on veterans' drug abuse symptoms. Depressive symptoms significantly mediated the trauma–drug abuse association. PTSS did not significantly mediate the trauma–drug abuse association. No gender differences were found. Abstract: Background: The current study was undertaken to examine whether posttraumatic stress symptoms (PTSS) and depressive symptoms mediated the association between trauma exposure (combat-related trauma and non-combat traumas occurring before, during, and after military service), and drug abuse symptoms use among male and female veterans. Methods: Participants were 2304 (1851 male, 453 female) veterans who took part in a multi-site research study conducted through the Department of Veterans Affairs Mid-Atlantic Mental Illness Research, Education and Clinical Center (VISN 6 MIRECC). Path analytic models were used to determine the association between problematic past-year drug use and combat-related and non-combat trauma experienced before, during, or after the military and whether current post-traumatic stress symptoms or depressive symptoms mediated these associations. Results: For both male and female veterans, depressive symptoms significantly mediated the effects of pre- and post-military trauma on drug abuse symptoms. Conclusion: Mental health providers who work with trauma-exposed Iraq and Afghanistan era veterans should assess for drug use, depressive symptoms, and life-span trauma (i.e., not only combat-related traumas) as part of a thorough trauma-based assessment for both men and women.